Distal Versus Conventional Radial Access for Coronary Angiography and Intervention: The DISCO RADIAL Trial - Aminian, Adel; Sgueglia, Gregory A; Wiemer, Marcus; Kefer, Joëlle; Gasparini, Gabriele L; Ruzsa, Zoltan; van Leeuwen, Maarten A H; Ungureanu, Claudiu; Leibundgut, Gregor; Vandeloo, Bert; Kedev, Sashko; Bernat, Ivo; et al. (Elsevier BV, 2022)
Currently, transradial access (TRA) is the recommended access for coronary procedures because of increased safety, with radial artery occlusion (RAO) being its most frequent complication, which will increasingly affect patients undergoing multiple procedures during their lifetimes. Recently, distal radial access (DRA) has emerged as a promising alternative access to minimize RAO risk. A large-scale, international, randomized trial comparing RAO with TRA and DRA is lacking.